2017
DOI: 10.1103/physrevb.96.085205
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band anisotropic electronic structure of ReS2

Abstract: We have used angle-resolved photoemission spectroscopy to investigate the band structure of ReS 2 , a transitionmetal dichalcogenide semiconductor with a distorted 1T crystal structure. We find a large number of narrow valence bands, which we attribute to the combined influence of structural distortion and spin-orbit coupling. We further show how this leads to a strong in-plane anisotropy of the electronic structure, with quasi-one-dimensional bands reflecting predominant hopping along zigzag Re chains. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
36
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 54 publications
12
36
2
1
Order By: Relevance
“…The proposed methods, which combines structure-search-based lithiation processes followed by delithiation, may be applied to other 2D materials to assess their suitability as LIB anodes. Figure 1a and b illustrate the top and side view of a fully relaxed 2×2 unit cell of ReS 2 with lattice parameters a = 6.42 Å, b = 6.52 Å, α = 91.88, β = 103.49̊and γ = 118.85̊(see Supplementary Note 1, Supplementary Figure 1), which agree with the previous reports 1, 31,32,42 . The pink shaded region indicates the intracluster area where clustering of Re atoms can be observed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The proposed methods, which combines structure-search-based lithiation processes followed by delithiation, may be applied to other 2D materials to assess their suitability as LIB anodes. Figure 1a and b illustrate the top and side view of a fully relaxed 2×2 unit cell of ReS 2 with lattice parameters a = 6.42 Å, b = 6.52 Å, α = 91.88, β = 103.49̊and γ = 118.85̊(see Supplementary Note 1, Supplementary Figure 1), which agree with the previous reports 1, 31,32,42 . The pink shaded region indicates the intracluster area where clustering of Re atoms can be observed.…”
supporting
confidence: 88%
“…To the best of our knowledge, no investigations on Li ion binding in ReS 2 based on first-principles have been reported yet, perhaps owing to the following reasons. (i) Due to distorted crystal structure, the number of atoms in ReS 2 unit cell is much higher 5,31,32 than any other 2D material with symmetric crystal structure. This imposes higher computation budget to study Li ion adsorption on ReS 2 .…”
mentioning
confidence: 99%
“…These figures are significantly reduced in comparison to other TMDCs such as MoS2 (57 GPa 78 ), MoSe2 (62 GPa 79 ), WS2 (63 GPa 80 ) or WSe2 (72 GPa 81 ). On the other hand, photoemission experiments 23,69,70 showed that there exist a significant electronic dispersion along the van der Waals gap and conclude that layers in ReX2 are not completely electronically decoupled. Also, recent calculations showed that the fundamental band gap of ReS2 (ReSe2) strongly depends on the number of layers, which shifts from 2.38 eV (2.05 eV) for monolayers down to 1.60 eV (1.38 eV) for bulk, and remains direct.…”
Section: First-principle Calculationsmentioning
confidence: 99%
“…Rhenium disulfide (ReS 2 ), a fresh member of group VII‐TMDs, is also an anisotropic 2D material but with little exploration. ReS 2 has distinct physicochemical properties owing to its unique 1T distorted structure and weak interlayer coupling . It also maintains a direct bandgap from monolayer to the bulk, without the band gap transition which group VI TMDs undergo .…”
Section: Introductionmentioning
confidence: 99%